The correct account of nonzero differential conductance in the saturation regime in the MOSFET compact model. (29th January 2014) - Turin, Valentin; Zebrev, Gennady; Makarov, Sergey; Iñiguez, Benjamin; Shur, Michael; Crupi, Giovanni; Schreurs, Dominique; Caddemi, Alina
SUMMARY We suggest a simple and versatile approach for the correct account of differential conductance in the saturation regime that provides a monotonic decrease of the differential conductance from its maximum value to its minimum positive or even negative value. We present all equations also in normalized form, which simplifies the analysis and usage of the approach. On the basis of the suggested approach, we have developed 'internal' (does not include source and drain resistance) metal–oxide–semiconductor field‐effect transistor compact model and have incorporated one into an Electronic Design Automation software Symica as Verilog‐A module. Copyright © 2014 John Wiley & Sons, Ltd.